2020
DOI: 10.4317/jced.56590
|View full text |Cite
|
Sign up to set email alerts
|

Hot air stream reduces cytotoxicity of light-cured calcium hydroxide based cements

Abstract: Background: The light-cured calcium hydroxide based cements have incomplete polymerization and unconverted monomers can cause pulp cell damage. The aim of this study was to evaluate the influence of a warm and hot air stream on the cytotoxicity of light-cured calcium hydroxide based cements. Material and Methods: The materials Dycal (conventional cement), Biocal, Hidrox-Cal, and Ultra-Blend Plus (light-cured calcium hydroxide cements) were submitted to cytotoxicity analysis after polymerization, without vs. wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Resin-modified calcium hydroxide or calcium silicate cements are promising dental products for pulp protection 7 . However, it is believed that the release of unpolymerized monomers has great impact on cytotoxicity in pulp cells by both direct and indirect contact, by diffusion of the monomers through the transdental route to the pulp tissue 12,13,18 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resin-modified calcium hydroxide or calcium silicate cements are promising dental products for pulp protection 7 . However, it is believed that the release of unpolymerized monomers has great impact on cytotoxicity in pulp cells by both direct and indirect contact, by diffusion of the monomers through the transdental route to the pulp tissue 12,13,18 .…”
Section: Discussionmentioning
confidence: 99%
“…A study by Daronch et al (2005) used a device that heats composite resin before use, which increased monomer conversion without increasing intrapulp temperature when compared to composites placed at room temperature, showing that the preheated composite can be used safely 10 . In order to increase the conversion of monomers, several studies have used different polymerization methods, reporting improvements in the physical and biological properties of heated resinous materials [11][12][13] . Studies have shown that resinous materials are cytotoxic, with harmful effects on the pulp, but further studies are needed on the use of photopolymerizable calcium-based cements.…”
Section: Introductionmentioning
confidence: 99%
“…Cell viability was assessed by analyzing mitochondrial activity using the methyl tetrazolium test (MTT) technique. The extracts were placed in contact with the cell culture, as described by Klein-Junior et al 20 The percentage of viable cells was calculated compared to the negative control, where the cells received no treatment, and the cytotoxicity grade was classified according to ISO 10993-5 (E) ( Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…When the professional is faced with very deep cavities, but without the exposure of the pulp tissue, it is necessary to perform indirect pulp capping in order to protect the pulp against future aggressive agents from polymeric and external restorative materials (SOARES et al, 2016). To perform this technique, liner materials are used that act as a protective base of the pulp-dentin complex against cytotoxic agents from resin materials (KLEIN-JUNIOR et al, 2018;KLEIN-JUNIOR et al, 2020a;KLEIN-JUNIOR et al, 2020b;BORGHETTI et al, 2020;ZIMMER et al, 2021). In cases where there is pulp exposure, direct pulp protection is done with the application of a capping agent over the exposed pulp tissue, with the objective of providing the formation of a dentin barrier, in addition to protecting the pulp from irritation from the external agents (SMITH et al, 2012;ARANDI, 2017).…”
Section: Introductionmentioning
confidence: 99%